HUBUNGAN NILAI KESAMAPTAAN JASMANI DENGAN NILAI KAPASITAS VITAL PARU PADA BATALYON PASKHAS 461 JAKARTA - Nency Sri Ulina Tarigan, (2015)
Battalyon Paskhas 461 based in Halim Air Force Base, Jakarta, under the guidance of Fr. Halim Air Base Wing 1 Main tasks carried Squadron 461 is also adapted to Paskhas status as kotamabin Air Force. In line with these basic tasks, where each person is always required in prime condition, we can see from the value kesamaptaan owned by their respective personnel, excellent physical condition requires the ability to kardirespirasi good, and it all can be seen from the ability of the respiratory system, where through the Vital Lung Capacity (KVP). This research is descriptive analytic using cross sectional study. The study was conducted in 461 Paskhas Battalion Halim Air Force. Sampling techniques using simple random sampling method the number of sampling 69 respondents. Data collection techniques using primary data in the form of Physical kesamaptaan Value calculation using the stopwatch and calculation of Vital Lung Capacity Value Spirometry test. Data were analyzed using chi square hypothesis test. Based on the results of the univariate test kesamaptaan Physical Data Value with value Samapta splendidly 8 respondents (11.6%), good value Samapta 54 respondents (78.3%), the value Samapta quite 7 respondents (10.1%), while the value of Vital Capacity Rated Capacity Vital lung Lung normal berkategorik as many as 62 respondents (89.9%), lung vital capacity value berkategorik restriction by 7 respondents (10.1%). Kolmogorov-Smirnov test results can be concluded there is a relationship (p = 0.0000) between Vital Lung Capacity (KVP) with the value of Physical kesamaptaan. Based on the results of the study need to be maintained even recommended to be increased in the guidance unit,in order to obtain a high kesamaptaan value.